2023
DOI: 10.1002/pits.22925
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity in kindergarten, fundamental movement skills, and screen time in Spanish preschool children

Abstract: Schools have been postulated as ideal environments to encourage physical activity (PA). This study aimed to assess the relationship between PA in school hours, motor competence, and screen time in a sample of Spanish preschool children. Fifty‐seven 4–5‐year‐old preschoolers (n = 32 girls) participated. The Garmin Vivofit wristband was used to measure the PA levels during school hours in a week. Sedentary behavior was estimated through screen‐time hours reported by preschoolers' families and motor competence wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 56 publications
1
2
0
Order By: Relevance
“…These findings are consistent with previous studies highlighting the positive potential of play and circuit-based approaches in improving motor skills in children with a variety of challenged motor conditions (Malika et al, 2022;Sistiarini, 2021). This study confirms that the use of game circuit-based fundamental motor skill activities can be an effective solution in stimulating gross motor development of children with dyspraxia (Carballo-Fazanes et al, 2023;Kasih, 2018).…”
Section: Pretest and Postestsupporting
confidence: 92%
“…These findings are consistent with previous studies highlighting the positive potential of play and circuit-based approaches in improving motor skills in children with a variety of challenged motor conditions (Malika et al, 2022;Sistiarini, 2021). This study confirms that the use of game circuit-based fundamental motor skill activities can be an effective solution in stimulating gross motor development of children with dyspraxia (Carballo-Fazanes et al, 2023;Kasih, 2018).…”
Section: Pretest and Postestsupporting
confidence: 92%
“…In contrast, the group (little sleep, little outdoor time, high screen) showed unhealthy behaviors (Rai et al, 2023). The study's results (Carballo-Fazanes et al, 2023) revealed a relationship between screen time and physical activity. The results of this study also support the need for specific strategies to promote screen time and increase physical activity practices from an early age because this will have a direct impact on children's health in the coming years.…”
Section: Article Reviewmentioning
confidence: 80%
“…The negative impact of screen time on the physical dimension of early childhood well-being includes impaired motor development and reduced food intake (Litterbach et al, 2023), shorter sleep duration (Zhang et al, 2021;Manousaki et al, 2020;Rai et al, 2023;Veldman et al, 2023), poor child health development (Carballo-Fazanes et al, 2023;Kerai et al, 2022), lower outdoor physical activity (Neville et al, 2021;Vale & Mota, 2020;Rai et al, 2023;Chia et al, 2022), tend to be overweight (Hu et al, 2021), addiction and poor vision (Chia et al, 2022). While only two studies state that there is no relationship between screen time and early childhood physical well-being, but support early health promotion that has an impact on early childhood physical well-being in the following year (Carballo-Fazanes et al, 2023;. In addition, from the journal search above, there are still few studies that link the impact of screen time with diet and nutrition (physical well-being) in early childhood.…”
Section: Discussionmentioning
confidence: 99%